2022
DOI: 10.3389/fgeed.2022.852867
|View full text |Cite
|
Sign up to set email alerts
|

Base Editors for Citrus Gene Editing

Abstract: Base editors, such as adenine base editors (ABE) and cytosine base editors (CBE), provide alternatives for precise genome editing without generating double-strand breaks (DSBs), thus avoiding the risk of genome instability and unpredictable outcomes caused by DNA repair. Precise gene editing mediated by base editors in citrus has not been reported. Here, we have successfully adapted the ABE to edit the TATA box in the promoter region of the canker susceptibility gene LOB1 from TATA to CACA in grapefruit (Citru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 72 publications
(131 reference statements)
1
27
0
Order By: Relevance
“…In the era of synthetic biology, with the fast expansion of the toolbox for modifying the genomes of living organisms, base-editing tools have attracted interest because of specific features: independence of endogenous cellular DNA repair pathways, lower cytotoxic effects than with other Cas9-based tools, high efficacy, which means that there is no need for selection markers, possibility of multitargeting, and the lack of a scar at the edited locus. These properties make BE promising tools for clinical usage in human therapeutics ( 60 ) and for multiple applications in plants ( 51 , 61 ) and microorganisms of medical or biotechnological relevance ( 62 64 ). Because of their high efficacy, BE are particularly attractive for bacteria that are difficult to transform, as, ultimately, one single transformant can be enough to obtain a mutant.…”
Section: Discussionmentioning
confidence: 99%
“…In the era of synthetic biology, with the fast expansion of the toolbox for modifying the genomes of living organisms, base-editing tools have attracted interest because of specific features: independence of endogenous cellular DNA repair pathways, lower cytotoxic effects than with other Cas9-based tools, high efficacy, which means that there is no need for selection markers, possibility of multitargeting, and the lack of a scar at the edited locus. These properties make BE promising tools for clinical usage in human therapeutics ( 60 ) and for multiple applications in plants ( 51 , 61 ) and microorganisms of medical or biotechnological relevance ( 62 64 ). Because of their high efficacy, BE are particularly attractive for bacteria that are difficult to transform, as, ultimately, one single transformant can be enough to obtain a mutant.…”
Section: Discussionmentioning
confidence: 99%
“…We first investigated if we could obtain transgene-free, gene-edited tomato in the T0 generation by base-editing SlALS1 (Solyc03g044330) alone. Previous studies suggested such a possibility, but the putative transgene-free plants were not confirmed by whole genome sequencing 10,15,28 . Here, we constructed the CBE-Cas12a-GFP-SlALS1 construct to edit the SlALS1 gene using CBE to target the proline residue at position 186 (Pro186) (Fig.…”
Section: Als Gene and Gene Of Interestmentioning
confidence: 93%
“…it is integrated into the plant genome because of their asexual reproduction nature through apomixis 9,10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic expression of antimicrobial peptides [13][14][15] , toxin 16 , resistance genes 17,18 , and immune-related genes [19][20][21][22][23][24][25] enabled increased canker resistance. Recently, CRISPR/Cas-mediated genome editing of the promoter or coding region of LOB1 has conferred citrus resistance to Xcc [26][27][28][29][30][31][32] . However, the citrus plants generated by transgenic overexpression and CRISPR genome editing approaches were all transgenic.…”
mentioning
confidence: 99%